2015
DOI: 10.1016/j.gmit.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Localized leiomyosarcoma of the uterine cervix with rapid lung metastases

Abstract: Keywords: immunohistochemistry leiomyosarcoma lung metastases smooth muscle cells uterine cervix a b s t r a c t Cervical sarcomas are extremely rare tumors associated with a poor prognosis. We report the case of a 63-year-old woman who was admitted to our institution due to abnormal vaginal bleeding and abdominal pain. Physical examination revealed a large cervical mass that was biopsied. Pathological features were compatible with a leiomyosarcoma of the uterine cervix. The patient underwent total abdominal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Therefore, the initial treatment should be surgery including hysterectomy with or without BSO. 29 Type of hysterectomy (extrafascial, modified radical, or radical) was not a prognostic indicator for recurrence but having hysterectomy performed had statistical significance for predicting DSS in our study. Likewise, Wright et al 1 concluded that different hysterectomy types do not improve survival in all types of cervical sarcomas.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore, the initial treatment should be surgery including hysterectomy with or without BSO. 29 Type of hysterectomy (extrafascial, modified radical, or radical) was not a prognostic indicator for recurrence but having hysterectomy performed had statistical significance for predicting DSS in our study. Likewise, Wright et al 1 concluded that different hysterectomy types do not improve survival in all types of cervical sarcomas.…”
Section: Discussioncontrasting
confidence: 60%
“…Amongst these factors, stage, grade and mitotic index were more significant prognostic factors. 5 An 18-year-old female gravida 3 para 1011 presented to an outside clinic with several months of vaginal bleeding and abdominal pain. She was diagnosed with an intrauterine pregnancy with an estimated gestational age (EGA) of 27 weeks based on dating by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Casanova et al [ 6 ] reported a case of localised leiomyosarcoma of the cervix in a 63-year-old woman who presented with lung metastasis after 1 year of diagnosis. There are various prognostic factors including tumour stage, grade, mitotic index, tumour size, age and menopausal status.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…There are various prognostic factors including tumour stage, grade, mitotic index, tumour size, age and menopausal status. Amongst these factors, stage, grade and mitotic index were more significant prognostic factors [ 6 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation